Silk‐elastin‐like protein polymer matrix for intraoperative delivery of an oncolytic vaccinia virus. Issue 2 (16th June 2015) - Price, Daniel L.; Li, Pingdong; Chen, Chun‐Hao; Wong, Danni; Yu, Zhenkun; Chen, Nanhai G.; Yu, Yong A.; Szalay, Aladar A.; Cappello, Joseph; Fong, Yuman; Wong, Richard J.
Abstract: Background: Oncolytic viral efficacy may be limited by the penetration of the virus into tumors. This may be enhanced by intraoperative application of virus immediately after surgical resection. Methods: Oncolytic vaccinia virus GLV‐1h68 was delivered in silk‐elastin‐like protein polymer (SELP) in vitro and in vivo in anaplastic thyroid carcinoma cell line 8505c in nude mice. Results: GLV‐1h68 in SELP infected and lysed anaplastic thyroid cancer cells in vitro equally as effectively as in phosphate‐buffered saline (PBS), and at 1 week retains a thousand fold greater infectious plaque‐forming units. In surgical resection models of residual tumor, GLV‐1h68 in SELP improves tumor control and shows increased viral β‐galactosidase expression as compared to PBS. Conclusion: The use of SELP matrix for intraoperative oncolytic viral delivery protects infectious viral particles from degradation, facilitates sustained viral delivery and transgene expression, and improves tumor control. Such optimization of methods of oncolytic viral delivery may enhance therapeutic outcomes. © 2014 Wiley Periodicals, Inc. Head Neck 38: 237–246, 2016